PENAFSIRAN FILOSOFIS TENTANG MIMPI DALAM PEMIKIRAN AL-KINDI: PERSPEKTIF ISLAM DAN KAJIAN FILSAFAT - Elmuna, Labib (Prodi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Filsafat UIN Alauddin Makassar, 2024)
This article delves into the concept of dreams in Islamic thought, particularly through the philosophical approach developed by Al-Kindi, an early Muslim thinker. Dreams have long been a focus of study in various civilizations, including the rich philosophical and spiritual traditions of Islam. In works such as